The Grammar of Internet Language - Stamboni, Juan Luis (2015)
It would not be amiss to say that the Internet is an electronic medium which facilitates and constrains our ability to communicate in ways that are different from those found in other semiotic situations. Although the Internet enables people to interact electronically with as much ease as they do in person, what is obvious when engaging in any of the Internet’s functions is its linguistic character. “Internet culture is still largely a text-based affair,” points out David Crystal. That is why it is the task of the linguist to analyse the role of language in the Internet as well as the effect of the Internet on language.